Nanoemulsions as topical delivery for anti-psoriatic drugs (subject review) - Ahmed Hamad Saleh; Jassim Mohamed Khalaf; Kameran Ahmed Ameen (Genius Journals, 2022)
Psoriasis is an autoimmune disease in which hereditary and environmental factors play a key influence, with an estimated global prevalence of 2–5%. Furthermore, available treatment methods are linked to both an unflattering visual look and toxicities, resulting in poor patient compliance over time. The potential for nanotechnology-based drug delivery systems to improve the bioavailability and effectiveness of pharmaceuticals in their dose forms, particularly lipophilic medications, is enormous. The lipid imbalance and normal moisturizing factors can be overcome with a lipid-based carrier system. Nanoemulsions, as a novel carrier, appear to have the potential to solve a number of issues associated with topical anti-psoriatic therapy. This delivery technique could be a viable option for treating psoriasis on the skin
Keywords: Psoriasis; Nanotechnology; Nanoemulsions